The Phenomenon of Student Violence Against Teachers in Indonesia: An Epistemological Perspective - Dinda Aulia; Rahma Fithri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The increasing incidence of student violence against teachers in recent years indicates a serious problem in educational relationships in Indonesia. This study aims to analyze student violence toward teachers from a epistemology perspective. This research employed a literature review method by systematically examining national and international scholarly journals, academic books, and official institutional reports relevant to the research topic. Data were analyzed using thematic and critical analysis to identify conceptual patterns, epistemic mechanisms, and research gaps in studies on school violence. The findings reveal that student violence toward teachers is not solely influenced by psychosocial and disciplinary factors, but also by the weakening of students’ epistemic trust in teachers, the relativization of epistemic authority due to digital media exposure, and the emergence of epistemic misalignment and epistemic injustice within pedagogical relationships. The shift in the knowledge ecology in the digital era has made students more selective and conditional in accepting teacher authority, causing disciplinary actions to be perceived as illegitimate. These findings highlight the importance of an epistemological approach in understanding and preventing school violence through strengthening epistemic trust, digital literacy, and dialogical disciplinary models.